Safety of Rapid Daratumumab Infusion: A Retrospective, Multicenter, Real-Life Analysis on 134 Patients With Multiple Myeloma - Bonello, Francesca; Rocchi, Serena; Barilà, Gregorio; Sandrone, Michela; Talarico, Marco; Zamagni, Elena; Scaldaferri, Matilde; Vedovato, Susanna; Bertiond, Cecilia; Pavan, Laura; Bringhen, Sara; Cattel, Francesco; et al. (Frontiers in Oncology, 2022)
Background The anti-CD38 monoclonal antibody daratumumab is the backbone of most anti-multiple myeloma (MM) regimens. To mitigate the risk of infusion-related reactions (IRRs), intravenous daratumumab administration requires 7 hours for the first infusion and 3.5-4 hours thereafter, thus making daratumumab-containing regimens burdensome for patients and health care resources. Preliminary data suggest that a rapid (90-minute) infusion of daratumumab is safe and does not increase IRRs. The rapid schedule was adopted by our centers since 2019. Methods We conducted an observational multi-center, real-life study to assess the safety of rapid daratumumab infusion protocol from the third administration in relapsed MM patients receiving daratumumab alone or in combination with lenalidomide-dexamethasone or bortezomib-dexamethasone. The primary endpoint was the safety of the rapid infusion protocol, particularly in terms of IRRs. Results A total of 134 MM patients were enrolled. IRRs occurred in 7 (5%) patients and were mostly mild (6/7 of grade 1-2), with only 1 patient experiencing a grade 3 IRR. Due to the IRRs, 5 (3.7%) patients discontinued the rapid infusions and resumed daratumumab at the standard infusion rate, while 1 patient permanently discontinued daratumumab. In 4/7 patients (57%), IRRs occurred while resuming rapid daratumumab infusions after a temporary interruption (2-4 months). No other adverse event was considered related to the rapid infusion protocol. Conclusions Our findings confirmed the safety of rapid daratumumab infusions starting from the third administration. In case of prolonged daratumumab interruption, it is advisable to resume infusions at the standard rate (3.5 hours) before switching to the rapid infusion.